An Amish patchwork : Indiana's Old Orders in the modern world - Meyers, Thomas J., 1952- (Indiana University Press, 2005)
Offers an overview of the Amish and Mennonite communities in Indiana, describing the traditions, beliefs, and contributions of each community and discussing their impact on the state's history.